Evaluating the 3-month post-intervention impact of a supportive text message program on mental health outcomes during the 2023 wildfires in Alberta and Nova Scotia, Canada - Obuobi-Donkor, Gloria; Shalaby, Reham; Agyapong, Belinda; Dias, Raquel da Luz; Eboreime, Ejemai; Wozney, Lori; Agyapong, Vincent Israel Opoku (Frontiers in Public Health, 2024)
BackgroundIndividuals exposed to wildfires are at risk of developing adverse mental health conditions in the months following the event. Receiving supportive text interventions during and after a wildfire event can have a significant impact on reducing mental health conditions over time.ObjectivesThe study aimed to assess the effectiveness of a supportive text message intervention service in reducing the severity and prevalence of psychological conditions 3 months following the 2023 wildfires in Alberta and Nova Scotia, two regions heavily affected by these natural disasters.MethodsIn this longitudinal study, participants voluntarily subscribed to the Text4Hope-AB and Text4Hope-NS services, receiving supportive text interventions for 3 months. On enrolment and at 3 months post-enrolment, participants completed online surveys. The severity and prevalence of mental wellbeing, resilience, depression, anxiety, and post-traumatic stress were measured using the World Health Organization- Five Well-Being Index (WHO-5), Brief Resilience Scale (BRS), Patient Health Questionnaire 9 (PHQ-9), Generalized Anxiety Disorder - 7 scale (GAD-7), and Post-Traumatic Stress Disorder Checklist for Civilians (PCL-C) respectively. Data analysis involved using McNemar’s chi-square test and paired sample t-tests.ResultsA total of 150 subscribers partially or fully completed both the baseline and 3-month assessments. The results show a statistically significant change in the mean scores on the WHO-5 Wellbeing Index (+ 24.6%), PHQ-9 (−17.0%), GAD-7 scale (−17.6%), PCL-C (−6.0%), and BRS (+3.2%) from baseline to 3 months. Similarly, there was a reduction, although not statistically significant, in the prevalence of low resilience (55.1 vs. 53.4%), poor mental well-being (71.6 vs. 48.3%), likely MDD (71.4 vs. 40.7%), likely GAD (42.1 vs. 33.3%), and likely PTSD (42.0 vs. 38.4%).ConclusionThe study’s findings underscore the potential of the supportive text intervention program in effectively aiding individuals who have endured natural disasters such as wildfires. Providing supportive text messages during wildfire events is a promising strategy for mitigating mental health conditions over time.